The dependence of cosmological parameters estimated from the microwave background on non-gaussianity - Amendola, Luca (Arxiv, 2001)
The estimation of cosmological parameters from cosmic microwave experiments has almost always been performed assuming gaussian data. In this paper the sensitivity of the parameter estimation to different assumptions on the probability distribution of the fluctuations is tested. Specifically, adopting the Edgeworth expansion, I show how the cosmological parameters depend on the skewness of the C_l spectrum. In the particular case of skewness independent of the multipole number I find that the primordial slope, the baryon density and the cosmological constant increase with the skewness.